Simulation and control of reactive distillation. - Sneesby, Martin G. (Curtin University, 1998)
Reactive distillation has enormous potential for the economical synthesis of tertiary ethers. Methyl tert-butyl ether (MTBE) has been commercially produced with this technology since the early 1980s and it appears that the process also has application for Ethyl tert-butyl ether (ETBE) and other ethers. However, the combination of reaction and distillation in a single unit operation produces a process complexity that inhibits expeditious design and tight control, and presents a technology risk for potential developers. This particularly applies to hybrid reactive distillation where both reactive and non-reactive column sections are employed.The steady state simulation of a series of reactive distillation columns and processes for the production of ETBE and MTBE illuminated a number of important issues related to the optimal design techniques. Many of these issues are peculiar to reactive distillation and would not reasonably be anticipated without a priori knowledge of the phenomena involved. For example, the addition of theoretical equilibrium stages and an increase in the reflux ratio do not always have a directionally equivalent effect. The trade-off between energy consumption and capital cost which is the basis for most distillation designs cannot always be applied to reactive distillation. Importantly, the use of standard modelling techniques for equilibrium processes was also validated for reactive distillation design.The use of residue curve diagrams and reactive residue curve diagrams for the design of reactive distillation processes was investigated and shown to provide useful information regarding the feasibility of reaction-separations. Combined with simulation tools (e.g. Pro/II and SpeedUp), these techniques form the basis of a proposed design strategy for hybrid reactive distillation. It is important to apply these design tools appropriately and to select the correct process for a given application. The optimal design must also consider economics and the relative values of products, reactants and energy. These issues were studied with respect to ETBE production for gasoline oxygenation.The complexity of hybrid reactive distillation not only presents design challenges but potentially makes the process more difficult to control. Dynamic simulations of ETBE and MTBE reactive distillation processes were used to explore some unusual dynamic phenomena and to elucidate the process non-linearity and bidirectionality of reactive distillation. The presence of multiple steady states for some reactive distillation columns has been documented previously but the analysis of this behaviour has been incomplete and somewhat flawed. It was shown that the distinction between molar inputs and physically realisable mass or volumetric inputs is crucial and that multiplicity could be present in one case and not in the other. Multiplicity that is only observed with molar inputs (relatively common) was termed pseudo-multiplicity. Pseudo-multiplicity has few implications for the operation and control of practical reactive distillation processes although most literature examples of multiple steady states fall into this category. Four distinct causes of output multiplicity were identified including one new cause, reaction hysteresis, which is only applicable to hybrid reactive distillation. It was shown, using dynamic simulations, that transitions between parallel steady states are possible for a range of physically realisable and practical disturbances. This contrasts with other work in the area, which examines only unrealisable events and control schemes.An extensive analysis of reactive distillation control was also undertaken with respect to ETBE and MTBE hybrid columns. Manual (open-loop) control was shown to be impractical due to the need to sustain the operating conditions at close to the optimal values in order to produce acceptable process performance. One-point composition control was found to be relatively easy to implement and effective with either an energy-balance or a material-balance control scheme provided only one steady state was present. Where multiple steady states exist, there are restrictions on the feasible control structures due to unavoidable instability in the inventory controllers. For example, if multiple steady states exist for the one value of the reboiler duty, only the bottoms product draw rate can be used to control the reboiler sump level. Thus, a material-balance control structure that uses the reboiler duty to control the sump level cannot be implemented in practice. Two-point control was also investigated and found to effectively prevent transitions between parallel steady states. Although more complex and difficult to implement than one-point control, a two-point scheme could be used successfully to control both the product composition and the reactant conversion and this could be desirable in some cases.A reactive distillation pilot plant was designed and operated for ETBE synthesis from ethanol and a locally available refinery hydrocarbon stream. The design of the pilot plant was based on simulation studies and the objective of operating in the industrially significant ranges of product purity and isobutene conversion. A fully automatic control system was designed and installed on the pilot plant to permit precise control of the manipulated variables and the framework to implement a range of control structures and schemes.Keywords: reactive distillation; process simulation; process design; process control; dynamic simulation; multiplicity; bidirectionality; distillation control; inferential control; pilot plant design and operation.